6: Biomimetic Microtissue Keloid Scar System Using Keloid-derived Fibroblasts and Macrophages. (July 2021) - Tan, Yu; Oles, Norah; Cooney, Damon; Andres Garza, Luis; Coon, Devin
Abstract : Purpose: Keloid is a disease that affects millions of patients and has relatively few effective treatment options. Unfortunately, traditional 2D monolayer culture of keloid derived fibroblasts show little resemblance to the pathological process in vivo. Additionally, keloid is notably a pathology largely specific to humans, without good in vivo models available. To fill this gap, we have developed a 3D in vitro microtissue keloid scar model with human keloid derived fibroblasts and peripheral blood derived macrophages. Methods: Under IRB approval, keloid tissue was from patients and used to develop a human keloid derived fibroblast line. Keloid spheroids were fabricated from these keloid derived fibroblasts and human peripheral blood derived macrophages. Commercial human skin-derived fibroblast and 2D monolayers were used as controls. Quantitative PCR with fibrosis genes (collagen-1, aSMA, TNF, IL1β, IL6 and TGFβ) and immunofluorescent staining with (collagen-1, aSMA, CD68 and pSTAT3 were performed to validate the keloid spheroids as an effective keloid model in vitro. In addition, we performed qPCR fibrosis microarray for fibrosis-specific gene expression. Lastly, the Affymetrix PrimeView array was used to evaluate genome-wide comprehensive gene expression to assess whether the keloid spheroid mimicking behavior of keloid tissue regarding gene expression level. Results: Spheroids had significantly higher expression levels of all fibrosis related genes compared to the 2D monolayer control. Among the spheroid groups, keloid spheroids had much higher gene expression levels of collagen-1 and aSMA, which was confirmed by the immunofluorescent staining with the same correspondence proteins. Interestingly, keloid spheroids showed lower gene expression levels of common fibrosis related cytokines (TNF, IL1β, IL6 and TGFβ). However, IF of pSTAT3 was upregulated in keloid spheroid, which is consistent with previous literature of keloid research. Lastly, qPCR fibrosis array and human comprehensive gene expression assay validated the result of qPCR and indicated that macrophages in the keloid spheroids showed signs of polarization in both M1 and M2 directions. Conclusions: We have developed a keloid mimicking spheroid microtissue as a more physiologically relevant in vitro keloid model for drug development and research exploring gene and protein expression pathways. This platform recapitulates important features of keloid behavior not seen in 2D culture. Future work will include screening of keloid spheroid responses to potential therapeutic treatments.